2004
DOI: 10.1016/j.jvs.2003.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Structured exercise improves calf muscle pump function in chronic venous insufficiency: a randomized trial

Abstract: Calf muscle pump function and dynamic calf muscle strength were improved after a 6-month program of structured exercise. Directed physical conditioning of the calf musculature may prove beneficial for patients with or without alternative management options for severe CVI. Further research on exercise for patients with CVI is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
234
2
28

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(271 citation statements)
references
References 26 publications
7
234
2
28
Order By: Relevance
“…Padberg et al concluded that structured exercise to reestablish calf muscle pump function in CVI may prove beneficial as a supplemental therapy to medical and surgical treatment in advanced disease. 68 …”
Section: Exercisementioning
confidence: 99%
“…Padberg et al concluded that structured exercise to reestablish calf muscle pump function in CVI may prove beneficial as a supplemental therapy to medical and surgical treatment in advanced disease. 68 …”
Section: Exercisementioning
confidence: 99%
“…Efficient peripheral pumps may compensate for some degree of reflux and obstruction and prevent chronic venous insufficiency symptoms (Padberg, Johnston et al, 2004;Plate, Brudin et al, 1986). It has been demonstrated that calf muscle strengthening exercises restore the pumping ability of the calf muscle and improve the haemodynamic performance in limbs with active ulceration subsequent to severe venous valvular and calf muscle pump impairment (Padberg, Johnston, et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…No relaxamento ela permite a oxigenação para o sangue. Sendo assim, uma alteração no funcionamento desta bomba devido à posição estática inadequada resultará no funcionamento defasado e, consequentemente, levará à fadiga muscular 13,14,15 .…”
Section: Artigo Original Saúde Funcionalunclassified